Lohmannella abyssalis Bartsch 2005 - Abé, Hiroshi (Zenodo, 2021)
Lohmannella abyssalis Bartsch, 2005 Diagnosis. Cornea absent. Glp-1 posterior to Ds-1. Ds-2 on AD. Ds-3 on membranous cuticle. Two dorsal setae on PE. Female with 17 Pgs and 6 Sgs. Tr I–IV with 1-1-1-1 setae; Bf I–IV with 2-3-3-3 setae; Tf I–IV with 4-5-3-3 setae; Gn I–IV with (7,8)-6-3-3 setae, 4-0-0-1 Bp setae; Tb I–IV with 9-8-5-5 setae, 5-1-1-2 Bp setae; Ta I–IV with 3-3-4-3 dorsal setae, 3-2-1-1 Bp setae. Lc I smooth. Idiosoma length 385 (holotype) in female, 330 in DN. Idiosoma width 299 (holotype). Gnathosoma length 233 (holotype). Gnathosoma width 104 (holotype). Ratio of gnathosoma to idiosoma 0.60 (holotype). Ratio of P-2 to P-1 4.20. Remarks. Most distinct characteristic is that palpi are situated dorsally, but distinctly separate each other. Other characteristics are that PE with 4 setae, 6 Sgs in female, Ds-2 situated on AD, P-2 with 1 spiniform ventral seta, and Gn I, Tb I, and Ta I with 4, 5, and 3 ventral Bp setae, respectively. Glps are small, although Lohmannella species of southern hemisphere generally have large Glps. Female and DN are known. Habitat. Bathyal zone (2893 m): Sediment at 0–10 cm depth from the surface. Distribution. Antarctic Ocean: Drake Passage and off the South Shetland Is. (60°38.464’S, 53°57.27’W) [Antarctica]. Reference. Bartsch (2005b). Depository. SMF. : Published as part of Abé, Hiroshi, 2021, Taxonomic review of the subfamily Lohmannellinae (Acari: Trombidiformes Halacaridae) with morphological comparisons among genera, pp. 201-255 in Zootaxa 4980 (2) on page 208, DOI: 10.11646/zootaxa.4980.2.1, http://zenodo.org/record/4888860 : {"references": ["Bartsch, I. (2005 b) Halacaridae from the depths of Western Antarctica (Arachnida: Acari). Senckenbergiana biologica, 85, 31 - 41."]}